ISOLASI DAN AKTIVITAS ANTIMIKROBA AKTINOMYCETES DARI TANAH KARST TAMAN WISATA BANTIMURUNG ASAL MAROS SULAWESI SELATAN - Fhahri Mubarak; Herlina Rante; Natsir Djide (As-Syifaa Jurnal Farmasi, 2017)
The increasing number of deaths caused by infection encourage researchers conduct early stage in the search for new antibiotics to resolve the issue. This study aims to isolate microbes aktinomicetes contained in karst areas of Bantimurung-tourist park district South Sulawesi province to see the antimicrobial inhibitory activity. The initial stage to get new antibiotics, researcher isolated, identified, characterized and tested the antimicrobial activity of isolates to be studied. One of microbes widely studied to be taken of its active compound is aktinomycetes. The research phase is actinomycetes isolation, isolates purification, and testing isolates antagonistic  actinomycetes  to see  whether  there  is a power resistor formed. From the results obtained 8 isolates  actinomycetes isolation, but only 6 isolates that can be grown back properly. Six of isolates  actinomycetes obtained, tested antagonist was done to see  the activity of inhibitory  power. Two of active isolateswas  obtained  that have  inhibitory  against  several  microbes  that P. aeruginosa and S. aureus which is then coded isolates of K21 and K32.